Unveiling Social Gratifications Sought and Obtained from Social Media Utilization - Raji, Ridwan Adetunji; Arikewuyo, Olawale Abdulgaffar; Oladimeji Adeyemi, Adeyemo Saheed; Pahore, Muhammad Ramzan (Universitas Semarang, 2020)
Going by the proposition of the Uses and Gratifications Theory (UGT), people are motivated to use media by various psychological factors and for obtaining different forms of gratifications. However, as social media continue to play an essential role in shaping the sociability and bridging social connectivity and interactions among its users, therefore, this study seeks to incorporate social influence and social interactions as the social gratification sought in social media utilization, as well as both bonding and bridging social capital as social gratification obtained from social media utilization. An online survey was conducted among 400 users of Instagram in Nigeria. The data analyzed with PLS-SEM revealed that social influence and social interaction significantly motivate social media utilization. Also, social media utilization is significantly associated with bonding and bridging social capital. Impliedly, this study shows that social media is a social and networking tool which is stimulated by social factors and for achieving social purposes such as getting help, support and community engagements.